An Introduction to Nanocrystal-Based Extended-release Injections - Thi Hai Yen, Tran; Khac Manh, Tran; Thi Minh Hue, Pham (VNU Journal of Science: Medical and Pharmaceutical Sciences; Acticle in Press, 2026)
Nanocrystals are carrier-free drug delivery systems consisting of pure drug particles exhibiting diameters under , coated by a thin layer of stabilizers. This article provides a comprehensive overview of nanocrystal-based extended injections, covering their fundamental concepts, drug release mechanisms, key excipients, and advanced manufacturing methods. The information from this review indicate that nanocrystals optimize drug loading capacity and enable the development of long-acting injectable formulations. This is achieved through the formation of primary or secondary "drug depots" at the injection site (intramuscular or subcutaneous administration) or passive accumulation in tumor tissues (intravenous administration). Furthermore, surface modification with specific ligands allows these nanosystems to bypass biological barriers and achieve active targeting. Regarding production, two primary manufacturing strategies top-down and bottom-up technologies are discussed. The information confirms the significant potential of nanocrystals in enhancing therapeutic efficacy and patient compliance for the treatment of chronic diseases, including schizophrenia, HIV, and cancer.